Thrombectomy outcomes for acute stroke patients with anterior circulation tandem lesions: a clinical registry and an update of a systematic review with meta‐analysis. (1st March 2018) - Sadeh‐Gonik, U.; Tau, N.; Friehmann, T.; Bracard, S.; Anxionnat, R.; Derelle, A.‐L.; Tonnelet, R.; Liao, L.; Richard, S.; Armoiry, X.; Gory, B.
Abstract : Background and purpose: Although mechanical thrombectomy (MT) appears to be superior in stroke patients with extracranial carotid disease (ECD) compared to thrombolysis alone, the impact of emergent carotid stenting during MT remains unclear. The MT outcomes were assessed in anterior stroke patients with ECD, especially when combined with carotid stenting. Methods: A retrospective analysis of our registry was performed and an update of a systematic review and meta‐analysis of MT studies with or without stenting for anterior circulation stroke with ECD published between November 2010 and April 2017 was conducted. Results: In our registry, 46 patients with ECD underwent MT. In the meta‐analysis including 13 primary studies plus our prospective registry data (590 patients in total), the successful reperfusion rate (modified thrombolysis in cerebral infarction score ≥2b) reached 75% [95% confidence interval (CI) 69%–81%]. The rate of symptomatic intracranial haemorrhage (sICH) was 8% (95% CI 6%–11%), 90‐day favourable outcome was achieved in 50% (95% CI 42%–59%) and mortality rate was 16% (95% CI 11%–22%). When using carotid stenting, rates of successful reperfusion, sICH, 90‐day favourable outcome and mortality were 80% (95% CI 73%–87%), 7% (95% CI 4%–12%), 53% (95% CI 43%–62%) and 14% (95% CI 9%–19%), respectively. Conclusions: Our data report an association between acute stenting and successful reperfusion rates in stroke patients with tandem lesion treated with MT. Further studies are warranted to determine the intracranial bleeding risk after MT and stenting according to the antiplatelet therapy.